Pengaruh Strategi Product, Price, Promotion terhadap Keputusan Nasabah Melakukan Pembiayaan pada PT BPRS Puduarta Insani Medan - Nur Ainun; Sandhi Fialy Harahap; Abdi Sugiarto (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
In the age of 4.0, the banking industry must be ready to change. This era changed the way people live, work and interact with one another. including the banking sector, which faces many challenges. The bank offers different types of products and business systems, but the Indonesian people are now more reluctant to use banking services, especially conventional banks that adhere to the interest rate system prohibited by Islam. As an alternative, Islamic banking was born, which implements a profit-sharing system. Many foreign banks entering the world of domestic banking offer innovative products that create fierce competition between banks and force banks to respond to changing customer preference patterns. The marketing mix helps to shape, develop and direct the mutually beneficial exchange between producers and consumers in the long term. The financing data of BPRS Puduarta Insani has tended to decrease since 2018. This study aims to determine the influence of product, price, promotion partially and simultaneously on purchase decisions for financing products. To find the variables that have the greatest impact on customer financing decisions, this study uses quantitative research and data analysis that uses the validity and reliability test, the T-test, and the F-test. The total population in this study was 900. The sample size was determined using the Solving formula with an error tolerance = 10%, so that the study sample obtained comprised 89 respondents. Methods of data collection through interviews and questionnaires to the respondents. The data analysis technique used in this study was multiple regression analysis with a significance level of 0.05. The results showed that product, price and advertising had a positive and significant influence on customer financing decisions at BPRS Puduarta Insani Medan.